Longitudinal mixed-methods analysis of tertiary students’ dropout considerations - Lykkegaard, Eva; Qvortrup, Ane (Frontiers in Education, 2024)
The paper presents a longitudinal mixed methods study investigating tertiary humanity students' dropout considerations, utilizing Tinto's institutional departure model as theoretical background. The research question is: How do students' dropout considerations take form and evolve throughout tertiary education? Methodically we have collected half-yearly register and survey data from 2,781 tertiary humanities students matriculating in 2017-2019. Additionally, we have conducted half-yearly interviews with 14 focus students that had high dropout considerations in the first survey round. Quantitative analysis of all humanity students and qualitative analysis of three case students are presented and discussed. The complementary analysis provides an in-depth understanding of the complex interplay between individual characteristics and institutional factors in shaping different students' dropout considerations and decisions in tertiary education. We find that there is a stable share of students with low, medium, and high dropout considerations throughout time. However, although we find stable shares, we identify primary movements from high dropout considerations towards dropout, and from low dropout considerations towards completion, we also find considerable secondary movement (i.e. from low dropout considerations towards dropout). As is also confirmed in the qualitative analyses, there are significant fluctuations in some students' dropout considerations. Dropout considerations are thus malleable and do not necessarily accumulate linearly over time to dropout. Individual students' dropout considerations change repeatedly in interaction with their experiences, their expectations for the future as well as with current challenges in meeting academic and personal requirements. Challenges are often about a lack of alignment between expectations and experiences and how well students and the study programs' norms and values match. We find students who seek to improve this match through personal transformations and others who try to change their study program. In both regards successfully improving the match seems to be a profitable strategy to prevent dropout.